2008
DOI: 10.1016/j.cub.2008.02.067
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Phage-Mediated Pigment Biosynthesis in Oceanic Cyanobacteria

Abstract: Although the oceanic cyanobacterium Prochlorococcus harvests light with a chlorophyll antenna [1-3] rather than with the phycobilisomes that are typical of cyanobacteria, some strains express genes that are remnants of the ancestral Synechococcus phycobilisomes [4]. Similarly, some Prochlorococcus cyanophages, which often harbor photosynthesis-related genes [5], also carry homologs of phycobilisome pigment biosynthesis genes [6, 7]. Here, we investigate four such genes in two cyanophages that both infect abund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
182
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(188 citation statements)
references
References 35 publications
2
182
0
Order By: Relevance
“…9,21 Changing to PebS was more effective, 22 as it generates PEB from biliverdin as a single enzyme. 32 The PebS-based approach allowed many GAFs of CBCRs to be chromophorylated with PEB ( Fig. 1, S2, S3; † Table 1).…”
Section: Autocatalytic Chromophorylation Of Gafs With Pebmentioning
confidence: 99%
“…9,21 Changing to PebS was more effective, 22 as it generates PEB from biliverdin as a single enzyme. 32 The PebS-based approach allowed many GAFs of CBCRs to be chromophorylated with PEB ( Fig. 1, S2, S3; † Table 1).…”
Section: Autocatalytic Chromophorylation Of Gafs With Pebmentioning
confidence: 99%
“…An emerging paradigm is that viruses also possess auxiliary metabolic genes (AMGs; Breitbart et al, 2007)-'host' genes that may be expressed to augment viral-infected host metabolism and facilitate production of new viruses (reviewed in Breitbart (2012) and Rohwer and Thurber (2009)). Due to the availability of cultures and genomes, AMGs are most extensively explored in marine cyanophages (viruses that infect cyanobacteria) and include genes involved in photosynthesis, carbon metabolism, phosphate metabolism and stress response (Mann et al, 2003;Lindell et al, 2004Lindell et al, , 2005Sullivan et al, 2005;Clokie et al, 2006;Sullivan et al, 2006;Weigele et al, 2007;Dammeyer et al, 2008;Millard et al, 2009;Thompson et al, 2011;Zeng and Chisholm, 2012;Frank et al, 2013). AMGs have also been observed in other cultivated viral isolates including genes for sugar metabolism, lipid-fatty acid metabolism and signalling (Derelle et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…For example, when discovered, viral pebS was most similar to a cyanobacterial pebA gene, which partners with the pebB product in phycoerythrobilin synthesis in the cyanobacterial host. Subsequent experimental work showed that this highly divergent viral PebS functionally replaces both host gene products (Dammeyer et al, 2008). Thus AMGs may directly influence system productivity and biogeochemical cycling by metabolically reprogramming host cells during infection and accelerating host niche differentiation through horizontal gene transfer of viral-evolved AMGs (Lindell et al, 2004;Ignacio-Espinoza and Sullivan, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Viral-induced mortality of microorganisms in the ocean can affect microbial species composition (Thingstad, 2000) and alter the flux of nutrients and organic matter by increasing recycling of these materials through the microbial loop (reviewed by Fuhrman, 1999). Expression of viral auxiliary metabolic genes (sensu Breitbart et al, 2007), such as core photosystem genes, during infection may also substantially impact oceanic productivity (Lindell et al, 2005;Clokie et al, 2006;Lindell et al, 2007;Sharon et al, 2007;Dammeyer et al, 2008;Thompson et al, 2011). In addition, viral-mediated horizontal gene transfer can profoundly alter the evolution of oceanic microorganisms as has been demonstrated in marine cyanobacteria (for example, Lindell et al, 2004;Sullivan et al, 2006;Ignacio-Espinoza and Sullivan, 2012).…”
Section: Introductionmentioning
confidence: 99%